Fluorescent activity-based probe for the selective detection of Factor VII activating protease (FSAP) in human plasma. Issue 182 (October 2019) - Rut, Wioletta; Nielsen, Nis Valentin; Czarna, Justyna; Poreba, Marcin; Kanse, Sandip M.; Drag, Marcin
Abstract: The zymogen form of circulating Factor VII activating protease (FSAP) is activated by histones that are released as a consequence of tissue damage or excessive inflammation. This is likely to have consequences in a number of disease conditions such as stroke, atherosclerosis, liver fibrosis, thrombosis and cancer. To investigate the existence, as well as the concentration of active FSAP (FSAPa) in complex biological systems an active site probe is needed. We used Hybrid Combinatorial Substrate Library (HyCoSuL) to screen for natural and unnatural amino acids that specifically bind to P4-P2 pockets of FSAPa. This information was used to designing a fluorogenic substrate (Ac-Pro- D Tyr-Lys-Arg-ACC) as well as an irreversible, fluorogenic activity-based probe Cy5-6-Ahx-Pro- D Tyr-Lys-Arg P (OPh)2 . In normal human plasma the probe showed very low non-specific reactivity with some plasma proteins but upon activation of pro-FSAP with histones, strong labelling of FSAPa was observed. This labelling could be inhibited by aprotinin and was not found in the plasma of a subject that was homozygous for a polymorphism, which leads to loss of activity, or in plasma that was depleted of FSAP by antibodies. This 2nd generation substrate exhibited 6-fold higher catalytic efficiency than the 1st generation substrate and a much higher selectivity for FSAPa over other plasma proteases. This substrate and probe can be useful to detect and localize FSAPa in normal and pathological tissue and plasma to gain more insight into its functions. Highlights: FSAP substrate specificity was determined using Hybrid Combinatorial Substrate Library (HyCoSuL). HyCoSuL approach was used to develop more potent 2nd generation substrate for FSAP. The first activity-based probe to detect FSAP activity in situ was designed and synthesized.